2018
DOI: 10.1038/s41396-018-0097-x
|View full text |Cite
|
Sign up to set email alerts
|

Short-term dynamics and interactions of marine protist communities during the spring–summer transition

Abstract: We examined the short-term variability, by daily to weekly sampling, of protist assemblages from March to July in surface water of the San Pedro Ocean Time-series station (eastern North Pacific), by V4 Illumina sequencing of the 18S rRNA gene. The sampling period encompassed a spring bloom followed by progression to summer conditions. Several protistan taxa displayed sharp increases and declines, with whole community Bray-Curtis dissimilarities of adjacent days being 66% in March and 40% in May. High initial a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 82 publications
11
64
0
Order By: Relevance
“…These molecular approaches have been widely applied in protist studies in different aquatic ecosystems, including inland, oceanic and coastal waters, and extreme environments (e.g., de Vargas et al, 2015;Ainsworth et al, 2017;Zhang et al, 2017;Brannock et al, 2018). Community composition of planktonic protists may differ among offshore (e.g., de Vargas et al, 2015;Malviya et al, 2016), coastal regions (e.g., Bittner et al, 2013;Massana et al, 2015) and water depths (e.g., Pawlowski et al, 2011); further the community may shift over seasons as well as over smaller (days to weeks) time scales (e.g., Berdjeb et al, 2018;Nagarkar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These molecular approaches have been widely applied in protist studies in different aquatic ecosystems, including inland, oceanic and coastal waters, and extreme environments (e.g., de Vargas et al, 2015;Ainsworth et al, 2017;Zhang et al, 2017;Brannock et al, 2018). Community composition of planktonic protists may differ among offshore (e.g., de Vargas et al, 2015;Malviya et al, 2016), coastal regions (e.g., Bittner et al, 2013;Massana et al, 2015) and water depths (e.g., Pawlowski et al, 2011); further the community may shift over seasons as well as over smaller (days to weeks) time scales (e.g., Berdjeb et al, 2018;Nagarkar et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In ecological studies of protistan communities, one key goal is understanding the patterns of community biodiversity and structure, at both the spatial (Massana et al, 2015;Logares et al, 2018;Das et al, 2019) and temporal scales (Genitsaris et al, 2015;Berdjeb et al, 2018), which in turn requires investigation of the factors that shape the communities (Steele and Ruzicka, 2011;Wang et al, 2013;Monard et al, 2016;Xue et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…land cover) variables resulting in highly diverse marine, and microbial communities, even in relatively close geographical locations (Brattegard, 1980; Herlemann et al, 2011). Microbial marine communities are dynamic (Berdjeb et al, 2018; Henriques et al, 2006) arising from the temporally and spatially fluid aquatic gradients (Jakacki et al, 2017; Storesund et al, 2017). Despite this, the microbial communities within fjords of the southern hemisphere (particularly NZ) remain unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Bahram et al () provide empirical evidence that neutral processes play the dominant role in the distribution of soil microeukaryotes at local levels. Additionally, Berdjeb et al () argued that environmental factors provide limited predictability for marine protist community variability, while interspecific relationships and stochastic processes are relevant in explaining changes in the composition of protist communities at short temporal scales. However, Xue et al () demonstrated that both deterministic and stochastic processes play important roles in the assembly of eukaryotic plankton communities.…”
mentioning
confidence: 99%